Pengaruh Kompensasi Langsung Dan Tidak Langsung Terhadap Kinerja Aparatur : The Effect Of Direct And Indirect Compensation On Apparatus Performance - Firmansyah, Andrie; Gienardy, Melda; Binalu, Julio Perdana; Satolom, Aprilia (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2023)
The type of research used in this research is qualitative research which is quantitative so it uses a Likert scale. Data collection techniques used questionnaires, interviews and literature studies. The sample used was 18 respondents. The analytical tools used are multiple linear regression, correlation coefficient, coefficient of determination, t test and F test. The results of data processing show the form of a multiple linear regression equation Y = 9.766+ 0.435X1+0.699X2+e. The correlation coefficient has a value of 0.814, which shows that the relationship between compensation variables (X1,X2) has a very strong relationship to the performance variable (Y), namely 81.4%. The coefficient of determination of 0.6629 (66.29%) shows that the contribution of the independent variable compensation (X) to the dependent variable performance (Y), the remaining 0.3171 or 31.71% is influenced by other factors not examined in the research This. The results of the t test data analysis showed that the calculated t value for direct compensation was 3.664 with a t table value of 2.131 (t calculated > t table), while the t calculated value for indirect compensation was 1.670 with a t table value of 2.131 (t calculated < t table). Simultaneous F test results obtained an F value of 14,752 and sig 0.00. The results of this research show that each direct and indirect compensation has a significant influence together on the performance of the Nanga-Nangaon village apparatus, Bunta sub-district.